2013
DOI: 10.1128/iai.01212-12
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Glycerol and Phospholipid Transporters in Mycoplasma pneumoniae Growth and Virulence

Abstract: Mycoplasma pneumoniae, the causative agent of atypical pneumonia, is one of the bacteria with the smallest genomes that are nonetheless capable of independent life. Because of their longstanding close association with their human host, the bacteria have undergone reductive evolution and lost most biosynthetic abilities. Therefore, they depend on nutrients provided by the host that have to be taken up by the cell. Indeed, M. pneumoniae has a large set of hitherto unexplored transporters and lipoproteins that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 34 publications
(47 reference statements)
0
48
0
Order By: Relevance
“…Instead, following permanent adherence via the adherend to the respiratory tract epithelia, M. pneumoniae spreads microtubules and inserts them into host cells, enabling oxygen consumption, use of glucose, absorption of cholesterol, ingestion of amino acids and consumption of nutrients in host cells, causing injury to the host cells (22,23). …”
Section: Direct Damage Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, following permanent adherence via the adherend to the respiratory tract epithelia, M. pneumoniae spreads microtubules and inserts them into host cells, enabling oxygen consumption, use of glucose, absorption of cholesterol, ingestion of amino acids and consumption of nutrients in host cells, causing injury to the host cells (22,23). …”
Section: Direct Damage Mechanismsmentioning
confidence: 99%
“…M. pneumoniae also exerts its toxin-like effects through its metabolites, exotoxin and exotoxin-like toxic substances, lipids, lipopolysaccharides and membrane lipoprotein (28). Following the adherence of M. pneumoniae onto the surface of bronchial cells, with the cytoskeleton rearrangement, M. pneumoniae penetrates through the bronchial mucous membranes and releases nuclease and H2O2, which result in swelling, necrosis and a binding of bronchial epithelial cells, slower microvilli movement, structural deformation, and the termination of swinging, thereby inducing the infiltration of lymphocytes, plasma cells and monocytes (22,29). With the lack of superoxide dismutase and catalase in M. pneumoniae , the H2O2 and superoxide groups synthesized by M. pneumoniae , and the endogenous toxic oxygen molecules produced by the host cells, increase the intracellular oxygen pressure in the epithelium, which leads to oxidative stress and subsequent cell death (Fig.…”
Section: Direct Damage Mechanismsmentioning
confidence: 99%
“…These conditions of life are mirrored in the genome by the strongly reduced number of genes encoding regulatory proteins, and by the limited amounts of carbon sources that can be utilized by M. pneumoniae. Among the few catabolic pathways are glycolysis for the utilization of glucose and fructose and the pathway for the degradation of glycerophospholipids by a dedicated phosphodiesterase and the subsequent utilization of glycerol-3-phosphate (Hames et al, 2009;Schmidl et al, 2011;Großhennig et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Brennan and Feinstein showed that catalase activity in mice was essential to initially fight off infection caused by the murine respiratory pathogen Mycoplasma pulmonis but also enhanced the survival of the microorganisms later in the infection, suggesting a balance between the catalase-producing host and the peroxide-producing pathogen [8]. Like M. pulmonis , the human respiratory pathogen M. pneumoniae lacks catalase but produces H 2 O 2 through pathways utilizing glycerol or glycerophosphocholine [4,9]. …”
Section: Introductionmentioning
confidence: 99%